2011
DOI: 10.1111/j.1365-313x.2010.04441.x
|View full text |Cite
|
Sign up to set email alerts
|

OTP70 is a pentatricopeptide repeat protein of the E subgroup involved in splicing of the plastid transcript rpoC1

Abstract: SUMMARYOver 20 proteins of the pentatricopeptide repeat (PPR) family have been demonstrated to be involved in RNA editing in plant mitochondria and chloroplasts. All of these editing factors contain a so-called 'E' domain that has been shown to be essential for editing to occur. The presumption has been that this domain recruits the (unknown) editing enzyme to the RNA. In this report, we show that not all putative E-class PPR proteins are directly involved in RNA editing. Disruption of the OTP70 gene leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
85
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(93 citation statements)
references
References 50 publications
7
85
0
1
Order By: Relevance
“…ys1 mutation causes an abolished RNA editing site in rpoB transcript, which may lead to defective plastid-encoded plastid RNA polymerase activities (17). Similarly, in otp70, the splicing of rpoC1 is compromised, which also leads to abnormal plastidencoded plastid RNA polymerase activities (18). In addition to these two categories of genes, virescent mutants have also been observed at rather high frequency in our screens for yellow variegated (var2) suppressors (19).…”
mentioning
confidence: 85%
“…ys1 mutation causes an abolished RNA editing site in rpoB transcript, which may lead to defective plastid-encoded plastid RNA polymerase activities (17). Similarly, in otp70, the splicing of rpoC1 is compromised, which also leads to abnormal plastidencoded plastid RNA polymerase activities (18). In addition to these two categories of genes, virescent mutants have also been observed at rather high frequency in our screens for yellow variegated (var2) suppressors (19).…”
mentioning
confidence: 85%
“…Attempts to identify the in vivo RNA ligands have only been made for a few PPR proteins (Schmitz-Linneweber and Small, 2008;Okuda et al, 2009Okuda et al, , 2010Pfalz et al, 2009;Yu et al, 2009;Johnson et al, 2010;Chateigner-Boutin et al, 2011;Prikryl et al, 2011). Many of the postulated activities of PPR proteins still lack direct biochemical proof and thus leave open the possibility that their roles are more indirect than suspected and may require additional, unidentified factors.…”
Section: Ysa Encodes a Ppr Protein Essential For Chloroplast Biogenesmentioning
confidence: 99%
“…Although group II introns are considered to be ''self-splicing'' (Lambowitz and Zimmerly 2011), self-splicing has not been reported for any land plant chloroplast introns. In fact, 14 nuclear genes have been identified that are required for the splicing of group II introns in angiosperm chloroplasts (for review, see Falcon de Longevialle et al 2010;Chateigner-Boutin et al 2011;Watkins et al 2011). Each is required for the splicing of distinct, but overlapping intron subsets, and each intron has been shown to require multiple proteins.…”
Section: Introductionmentioning
confidence: 99%